THE EFFECT OF FREE FLOAT RATIO AND PROFITABILITY ON STOCK PRICE - Wiharti Arum Sari; Arif Nugroho Rachman (Berkala Akuntansi dan Keuangan Indonesia, 2021)
The Indonesian Stock Exchange in supporting and increasing the confidence of stock investors, it is deemed necessary to apply the Free Float as an adaptation to the market capacity used in calculating the LQ45 and IDX30 Indices in 2019. Free float is the total shares whose ownership is less than 5% based on data from PT Kustodion Sentral Indonesian Securities. Changes in LQ45 and IDX30 Index Methodology were announced by the IDX in the announcement letter attached to the IDX website with IDX letter number No: Pebng-00893 / BELOPP / 11-2018 dated 23 November 2018). The discussion in this research is whether share prices can be affected by , Free float ratios, and profitability ratios which include ROE, ROA and EPS in companies listed on the LQ45 index for the period 2015-2019. The population in this research is the corporations listed on the LQ45 index. The sample collection technique used purposive sampling, with a total of 19 companies. Multiple linear regression analysis is used by researchers as an analytical tool. Multiple linear regression analysis shows that the stock price (Y) is not affected by the free float ratio (X1) and ROA (X3). ROE (X3) affects the stock price (Y) negatively, while the stock price is positively affected by EPS (X4). The results in the determination coefficient table, the adjusted R² value is 0.633, so that the dependent variable, namely the stock price, is simultaneously affected by the independent variables, namely the Free Float Ratio, ROE, ROA and EPS with a value of 63.3%, while 36.7% is affected by the variables in outside of this research.